The long century's long shadow : Weimar cinema and the romantic modern - Calhoon, Kenneth Scott, 1956- (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
"The Long Century's Long Shadow approaches German Romanticism and Weimar cinema as continuous developments, enlisting both in a narrative of reciprocal illumination. The author investigates different moments and media as connected phenomena, situated at alternate ends of the "long nineteenth century" but joined by their mutual rejection of the neo-classical aesthetic standard of placid and weightless poise in numerous media, including film, painting, sculpture, prose, poetry, and dance. Connecting Weimar filmmaking to Romantic thought and practice, Kenneth S. Calhoon offers a non-technological, aesthetic genealogy of cinema. He focuses on well-known literary and artistic works, including films such as Nosferatu, Metropolis, Frankenstein, and Fantasia; the writings of Conrad, Kafka, Goethe, and Novalis; and the paintings of Caspar David Friedrich, one of the leading artists of German Romanticism. With an eye to the modernism of which Weimar filmmaking was a part, The Long Century's Long Shadow employs the Romantic landscape in poetry and painting as a mirror in which to regard cinema."--
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Introduction -- Chapter One. The Turmoil of Forces -- Chapter Two. Under the Sign of Insomnia -- Chapter Three. Nightwatching -- Chapter Four. A Pause in the Action -- Chapter Five. Facing the Image -- Chapter Six. Necessary Advances -- Chapter Seven. Music of the Third Kind: Fantasia and Faustus -- Filmography -- Notes -- Works Cited -- Index -- GERMAN AND EUROPEAN STUDIES.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 13, 2021).
JSTOR
Keywords: Motion pictures -- Germany -- History; Motion pictures, German -- History -- 20th century; Romanticism -- Germany; Art and motion pictures -- Germany; Motion pictures and literature -- Germany; Cinéma -- Allemagne -- Histoire; Cinéma allemand -- Histoire -- 20e siècle.; Romantisme -- Allemagne; Art et cinéma -- Allemagne; Cinéma et littérature -- Allemagne; LITERARY CRITICISM / European / German; Art and motion pictures; Motion pictures; Motion pictures and literature; Motion pictures, German; Romanticism; Germany; 1900-1999; Caspar David Friedrich; German romantic art; German romanticism; Goethe; Nosferatu; Weimar cinema; abstraction; empathy aesthetics; expressionism; modernism; psychoanalytic approaches to literature and film; Film criticism; History; Film criticism; Critiques cinématographiques.